Application Of Feed Acidifiers In Control Of Poultry Pathogens In Commercial Layers - Kannan, D.; Saravanan , S. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A field trail was conducted to assess the effect of liquid and powder form of acidifiers in feed for controlling Staphylococcus spp., Clostridium spp., E. coli and Salmonella spp. in poultry. All the feed samples used under trial were analyzed for the presence of above organisms before and after the addition of acidifier. Before adding acidifier, majority of the feed samples showed the presence of all organisms except Salmonella spp. After addition of acidifier in the same feed samples, presence of organisms were decreased to a significant level and hen housed egg production and in turn per bird profit were also increased.